Prognozowanie sprzedaży energii elektrycznej - Iwaniec, Magdalena Anna (Sale Forecasting of Electric Energy, 2007)
The need for forecasting various phenomena in a company results from its uncertain future. That is why forecasts have become an important element of company management process. Sales forecasting is especially of great importance. It makes possible to develop a sales plan that is a basis for other plans in a company. Forecasting in the electrical power engineering is one of the most important researches. It results from the specifity of electric energy and electric energy market. One of the factors influencing the demand for electric energy is the value of GDP. In the electrical power engineering there is demand for short- and long-period forecasting, but the first one is of greater importance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 223-230